IUTAM symposium on nonlinear stochastic dynamics and control Proceedings of the IUTAM Symposium held in Hangzhou, China, May 10-14, 2010 - Zhu, W. Q.(Wei-Qui); Lin,Y. K.(Yu-Kweng) 1923-; Cai, G.Q.(Gao-Qiang) (Springer Netherlands, 2011)
Non-linear stochastic systems are at the center of many engineering disciplines and progress in theoretical research had led to a better understanding of non-linear phenomena. This book provides information on new fundamental results and their applications which are beginning to appear across the entire spectrum of mechanics. The outstanding points of these proceedings are Coherent compendium of the current state of modelling and analysis of non-linear stochastic systems from engineering, applied mathematics and physics point of view. Subject areas include: Multiscale phenomena, stability and bifurcations, control and estimation, computational methods and modelling. For the Engineering and Physics communities, this book will provide first-hand information on recent mathematical developments. The applied mathematics community will benefit from the modelling and information on various possible applications.